Bone-marrow-derived endothelial progenitor cells contribute to vasculogenesis of pregnant mouse uterus. Issue 5 (2nd January 2019) - Tal, Reshef; Dong, Dirong; Shaikh, Shafiq; Mamillapalli, Ramanaiah; Taylor, Hugh S
Abstract: Angiogenesis is essential for cyclic endometrial growth, implantation, and pregnancy maintenance. Vasculogenesis, the formation of new blood vessels by bone marrow (BM)-derived endothelial progenitor cells (EPCs), has been shown to contribute to endometrial vasculature. However, it is unknown whether vasculogenesis occurs in neovascularization of the decidua during pregnancy. To investigate the contribution of BM-derived EPCs to vascularization of the pregnant uterus, we induced non-gonadotoxic submyeloablation by 5-fluorouracil administration to wild-type FVB/N female mice recipients followed by BM transplantation from transgenic mice expressing green fluorescent protein (GFP) under regulation of Tie2 endothelial-specific promoter. Following 1 month, Tie2-GFP BM-transplanted mice were bred and sacrificed at various gestational days (ED6.5, ED10.5, ED13.5, ED18.5, and postpartum). Bone-marrow-transplanted non-pregnant and saline-injected pregnant mice served as controls (n = 5–6/group). Implantation sites were analyzed by flow cytometry, immunohistochemistry, and immunofluorescence. While no GFP-positive EPCs were found in non-pregnant or early pregnant uteri of BM-transplanted mice, GFP-positive EPCs were first detected in pregnant uterus on ED10.5 (0.12%) and increased as the pregnancy progressed (1.14% on ED13.5), peaking on ED18.5 (1.42%) followed by decrease in the postpartum (0.9%). The percentage of endothelial cells that were BM-derived out of the total endothelial cell population in the implantation sites (GFP + CD31 + /CD31 + ) were 9.3%, 15.8%, and 6.1% on ED13.5, ED18.5, and postpartum, respectively. Immunohistochemistry demonstrated that EPCs incorporated into decidual vasculature, and immunofluorescence showed that GFP-positive EPCs colocalized with CD31 in vascular endothelium of uterine implantation sites, confirming their endothelial lineage. Our findings indicate that BM-derived EPCs contribute to vasculogenesis of the pregnant mouse decidua. Abstract : Bone marrow-derived endothelial progenitor cells contribute to decidual neovascularization of the pregnant uterus via vasculogenesis